THE IMPACT OF EXCHANGE RATES AND INFLATION ON STOCK PRICE VOLATILITY: EVIDENCE FROM THE INDONESIA SHARIA STOCK INDEX (ISSI) - Tasya Shafira Musthofa; Irham Fahmi; Azimah Dianah (J-ISCAN: Journal of Islamic Accounting Research, 2025)
The performance of the Indonesian sharia stock market is reflected in the Indonesian Sharia Stock Index (ISSI). The Indonesian Sharia Stock Index (ISSI) is a composite index of sharia shares listed on the Indonesia Stock Exchange (IDX). The aim of this research is to determine the simultaneous and partial impact of the Exchange Rate and Inflation factors on share price fluctuations in the Indonesian Sharia Stock Index (ISSI). This research uses a quantitative research methodology which includes library research and data collection through the Central Statistics Agency (BPS), the Financial Services Authority (OJK), and the Indonesian Stock Exchange (IDX). The data in this study uses times series data. The population of this study is the movement of stock prices on the Indonesian Sharia Stock Index (ISSI), Rupiah Exchange Rates and Inflation in the time period January 2018-December 2022 and as many as 60 monthly data from market capitalization values ​​on the Indonesian Sharia Stock Index (ISSI). The results of this research show that there is a simultaneous impact of the Rupiah Exchange Rate and Inflation on the Indonesian Sharia Stock Index (ISSI). The Rupiah exchange rate has a positive partial impact on the Indonesian Sharia Stock Index (ISSI), while inflation has a negative partial impact